2017
DOI: 10.1016/j.scitotenv.2017.07.056
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of electric lighting practices in the modern world: A report on the National Toxicology Program's workshop on shift work at night, artificial light at night, and circadian disruption

Abstract: The invention of electric light has facilitated a society in which people work, sleep, eat, and play at all hours of the 24-hour day. Although electric light clearly has benefited humankind, exposures to electric light, especially light at night (LAN), may disrupt sleep and biological processes controlled by endogenous circadian clocks, potentially resulting in adverse health outcomes. Many of the studies evaluating adverse health effects have been conducted among night- and rotating-shift workers, because thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
214
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(235 citation statements)
references
References 64 publications
4
214
0
2
Order By: Relevance
“…This stable LD cycle may have helped make the DLMOs more stable. Earlier reports suggest that under ecological conditions (outside the laboratory) the correlation between subjective sleep timing and objective circadian timing (DLMO) is rather noisy (Kantermann & Burgess, 2017; Kantermann, 2013; Kantermann et al, 2015; Lunn et al, 2017; Van Reen et al, 2013; Wright et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This stable LD cycle may have helped make the DLMOs more stable. Earlier reports suggest that under ecological conditions (outside the laboratory) the correlation between subjective sleep timing and objective circadian timing (DLMO) is rather noisy (Kantermann & Burgess, 2017; Kantermann, 2013; Kantermann et al, 2015; Lunn et al, 2017; Van Reen et al, 2013; Wright et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Circadian misalignment (sleeping, working, eating, etc. at the wrong phases of the internal circadian clock) results in poor sleep and health and performance decrements (Akerstedt et al, 1984; Archer & Oster, 2015; Gold et al, 1992; Kantermann et al, 2012; Lunn et al, 2017; McHill et al, 2017; Smith & Eastman, 2012). Hence, maintaining the proper alignment between circadian rhythms and the sleep schedule is essential for health and safety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of known and suspected hazards to wildlife ecology and human health have been identified that are thought to result from exposure to short-wavelength ALAN. [6,7,8] The spectrum shift in new SSL systems is also thought to yield increases to skyglow, which is the diffuse luminescence of the night sky attributable to light emitted from sources on the ground that is scattered back toward the ground from molecules and aerosols in the Earth's atmosphere. Enhanced short-wavelength light emissions associated with blue-rich white LED are subject to strong Rayleigh scattering in the atmosphere, resulting in higher scattering probabilities, associated with the formation of skyglow, than light of longer wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…A great deal of recent work in biology has illuminated the unexpected impacts of light on animal physiology (e.g. [1][2][3]), including that of humans [4]. Light has dramatic effects on animal behavior [5][6][7][8], and is in many cases deadly [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%